2014
DOI: 10.1308/003588414x13814021678673
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of renal artery pseudoaneurysm following partial nephrectomy

Abstract: A bleeding renal artery pseudoaneurysm is a recognised complication occurring after partial nephrectomy. The bleeding is usually suspected when a patient presents with haematuria following the procedure and the reported management is with radiologically guided embolisation. We report a case of renal artery pseudoaneurysm successfully managed conservatively, giving another potential management option in non-torrential haemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Darbyshire et al reported a case of renal artery pseudoaneurysm successfully managed conservatively, giving another potential management option in non-torrential hemorrhage. 4 …”
Section: Discussionmentioning
confidence: 99%
“…Darbyshire et al reported a case of renal artery pseudoaneurysm successfully managed conservatively, giving another potential management option in non-torrential hemorrhage. 4 …”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to not treat RAPs or AVFs if they are apparent. Although in rare cases bleeding due to RAP disappears spontaneously, Hyams et al reported that the rate of resolution with conservative management alone was 11% (Hyams et al 2011 ; Darbyshire et al 2014 ). Further studies are required to investigate what kind of RAPs or AVFs can in the future be managed with conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous rupture of the renal artery is a rare but documented event, and is usually preceded by pseudoaneurysmal formation. 9 , 10 The underlying etiology behind it can vary and has been reported to occur in various clinical scenarios including angiomyolipomas, renal cell carcinoma, acquired cystic kidney disease secondary to hemodialysis, a complication of surgery, or percutaneous procedures or preceded by an RAA. 10 - 16 …”
Section: Discussionmentioning
confidence: 99%